(untitled) (Iraqi Journal of Civil Engineering, 2018)
The use of textile reinforcement made from non-corrosive materials, such as carbon and glass can reduce the required concrete material; this is known as Textile Reinforced Concrete (TRC). This study deals with plate specimens having dimension of 500×500×40mm tested under impact load at 28 and 90 days age under two conditions of ends, simply supported and fixed. Cement mortar with about 60 MPa, 7cm cube compressive strength at 28 days was designed for casting the plates. Plate specimens were divided into four groups, they consist of reference plates (no reinforcement) and plates reinforced with 3D glass fabric having three different thicknesses 6, 10 and 15mm. The results indicate that using 3D textile glass fabric cause an increase in number of blows, reduce in final stage deflection, an improvement in toughness and energy absorption under impact loads. Using 3D textile glass fiber with 10mm thickness gave higher number of blows for 28 and 90 days as compared with 6 and 15 mm. Plates with slice 6mm 3D textile glass fiber in two way reinforced has significantly enhancement in number of blows, the improvement was about (80 - 125%) and (128.5- 114. 3%) for 28 and 90 days respectively. The specimens showed increase in the energy absorption, besides the number and width of cracks was reduced and only few cracks are propagated up to the edge of the plates.